Stratigraphy and eruptive model of the dacitic volcanism in the region of São Marcos (South Paraná Magmatic Province) - Guimarães, Letícia Freitas (2019)
Voluminous silicic volcanic rocks from the Paraná-Etendeka Magmatic Province are exposed in the southern Brazil, where a regional synformal structure (Torres Syncline) allowed the deposition and favored the preservation of a thick sequence of these units. In the São Marcos region (Rio Grande do Sul state) the volcanic sequence comprises basaltic rubbly pahoehoe flows (Vale do Sol Fm.) overlapped by dacitic deposits (Caxias do Sul sub-type), both intruded by basaltic dykes (Esmeralda Fm.). The genetic correlation between the Caxias do Sul dacites and the Vale do Sol basalts by an AFC process, already well described in the literature, is confirmed here; the fractionation of the basaltic magmas (with the extraction of plagioclase, pyroxene and Ti-magnetite) is clear through the patterns of major and trace elements, whereas the assimilation of crust is evidenced by variations in the traces elements ratios such as Rb/Ba and Th/U. Part of the chemical variations observed in the Caxias do Sul dacites were interpreted as primary, revealing the existence of two distinct groups of samples, with subtle variations in trace elements contents (Ce, Sm, Y and Th/U), suggestive of different sources and/or variations in the assimilated crustal component. Sub-parallel to the axis of the Torres Syncline, a NW-SE-trending zone constituted by the alignment of complex structures was interpreted as the feeding system of silicic volcanism, characterized as fissural. Detailed mapping allowed the description of distinct morphological domains, designated as \"breccia domain\", \"fragmentation domain\", \"regular domain\" and \"filaments domain\", the first domain being recognized as the host rock (together with underlying banded dacites) of the intrusive flow represented by the latter. The vertical intrusive flow exhibits two preferential directions: NW, ranging from N272° to N 355°, and NE, varying from N20° to N85°. The stratigraphy of the dacitic sequence can be defined, from the base to the top, as: banded deposits, classified as rheoignimbrites, and volcanic breccias locally intruded by the dacitic feeder system referred to above, followed by hybrid deposits (characterized by synchronous volcanic breccias and lobated lavas) which gradually give place to lavas flows and finally to massive deposits. Macroscopic quantitative textural analysis (including size distribution and shape parameters analysis of fragments and vesicles) of the volcanic breccias indicate that these deposits were generated under low eruptive energy and comparative studies support the hypothesis that they correspond to block and ash deposits. An eruptive model is proposed as follows: high temperature volatile-poor dacitic magma raised in a fissural conduit system with no significant crystallization. The low content (or even absence) of crystals and high temperatures inhibited the drastic increases in the viscosity of the shallow magmatic system. A magmatic rise fast enough to inhibit intense crystallization may have led to late-stage bubble growth and, together with high magma outflow rates, to boiling over eruptions responsible for the generation of PDCs (rheoignimbrites) related either to low-explosivity events or magma fountains. This first pyroclastic phase may have allowed efficient magma degassing and viscosity increase, and was succeeded by dome extrusions. The dome structure reduced the permeability and degassing of the system, leading to a new overpressure and causing the collapse of the dome structure and originating block and ash deposits. Additionally, the fissural architecture of the feeding system possibly permitted magma migration along an extended and variably open/closed fissure, leading to the occurrence of isolated magma batches evolving differently in terms of viscosity and degassing. This condition would be responsible for the occurrence of active and inactive vents, or vents with distinct eruptive dynamics spatially and/or temporally separated along the fissure system. Over time, the dome extrusion evolved towards new explosive events as relatively gas-rich magma ascent through the active shallow plumbing system or lava dome collapse caused rapid decompression and fragmentation. Finally, a gradual loss of eruptive energy and the widening of the active vent may have led to the explosive-effusive transition responsible for the generation of the hybrid deposits and lava flows.